Combining chemotherapy and tislelizumab with preoperative split-course hypofraction radiotherapy for locally advanced rectal cancer: study protocol of a prospective, single-arm, phase II trial. Issue 3 (16th March 2023) - Zheng, Rong; Wang, Bi-Si; Li, Zhihua; Chi, Pan; Xu, Benhua
Abstract : Introduction: Short-course radiotherapy (SCRT) with systemic therapy has the potential to further improve the long-term efficacy in patients with locally advanced rectal cancer (LARC). To maximise the benefits of neoadjuvant therapy for improved prognosis, it is important to determine the optimal mix of chemotherapy, immunotherapy and SCRT. Methods and analysis: Fifty treatment-naïve patients with operable LARC (T3–4 and/or N+) will be recruited. Patients will be synchronously treated with capecitabine plus oxaliplatin (CAPOX) chemotherapy, tislelizumab and preoperative split-course hypofraction radiotherapy (SCHR) (5×7 Gy) before surgery. Chemotherapy for CAPOX starts on day 1 of every 21-day cycle: on day 1, oxaliplatin 130 mg/m 2 will be injected intravenously. On days 1–14, capecitabine 1000 mg/m 2 was ingested two times a day. Simultaneously, tocilizumab 200 mg will be given intravenously on the first day of every 21-day cycle. A single 7 Gy SCHR treatment (day 7 of each 21-day cycle) will be delivered five times during the seventh day of treatment. The primary endpoint will be pathological complete response. The secondary outcomes will be the 3-year disease-free survival, local recurrence rate, overall survival, sphincter-sparing surgery rate, R0 resection rate, predictive biomarkers and quality of life. Ethics and dissemination: The study protocol was approved by the Ethics Committee of Xiehe Affiliated Hospital of Fujian Medical University (XAHFMU) (No. 2021YF025-01). Results from our study will be disseminated in international peer-reviewed journals. All study procedures were developed in order to assure data protection and confidentiality. Trial registration number: NCT05176964 .